2020
DOI: 10.1021/jacs.0c00287
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrolled Radical Polymerization from Hydridic C–H Bonds

Abstract: Given the ubiquity of C-H bonds in biomolecules and polymer backbones, the development of a photocontrolled polymerization from a C-H bond would represent a powerful strategy for selective polymer conjugation precluding several synthetic steps to introduce complex functionality. We have developed a hydrogen-atom abstraction strategy that allows for a controlled polymerization from a C-H bond using a benzophenone photocatalyst, a trithiocarbonate-derived disulfide, and visible light. We perform the polymerizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 33 publications
(55 reference statements)
2
42
0
Order By: Relevance
“…We reasoned that performing the copolymerization at lower temperatures would provide a key opportunity to modulate the reactivity ratios of vinyl comonomers. Therefore, we turned our attention to light‐mediated polymerization techniques, as recent works have demonstrated that they are versatile tools to mediate controlled polymerization following radical, [34–42] cationic, [43–47] and metathesis pathways [48–50] at ambient temperature (Figure 1B) [51] . In particular, we envisioned that the photoinduced electron/energy transfer‐reversible addition/fragmentation chain transfer (PET‐RAFT) polymerization developed by Boyer and co‐workers [52–56] could be employed to mediate the radical ring‐opening cascade copolymerization (rROCCP) [57, 58] of the macrocyclic allylic sulfone with acrylates or acrylamides (Figure 1C).…”
Section: Introductionmentioning
confidence: 99%
“…We reasoned that performing the copolymerization at lower temperatures would provide a key opportunity to modulate the reactivity ratios of vinyl comonomers. Therefore, we turned our attention to light‐mediated polymerization techniques, as recent works have demonstrated that they are versatile tools to mediate controlled polymerization following radical, [34–42] cationic, [43–47] and metathesis pathways [48–50] at ambient temperature (Figure 1B) [51] . In particular, we envisioned that the photoinduced electron/energy transfer‐reversible addition/fragmentation chain transfer (PET‐RAFT) polymerization developed by Boyer and co‐workers [52–56] could be employed to mediate the radical ring‐opening cascade copolymerization (rROCCP) [57, 58] of the macrocyclic allylic sulfone with acrylates or acrylamides (Figure 1C).…”
Section: Introductionmentioning
confidence: 99%
“…[6,33] We reasoned that performing the copolymerization at lower temperatures would provide a key opportunity to modulate the reactivity ratios of vinyl comonomers. Therefore, we turned our attention to light-mediated polymerization techniques, as recent works have demonstrated that they are versatile tools to mediate controlled polymerization following radical, [34][35][36][37][38][39][40][41][42] cationic, [43][44][45][46][47] and metathesis pathways [48][49][50] at ambient temperature (Figure 1B). [51] In particular, we envisioned that the photoinduced electron/energy transferreversible addition/fragmentation chain transfer (PET-RAFT) polymerization developed by Boyer and coworkers [52][53][54][55][56] could be employed to mediate the radical ringopening cascade copolymerization (rROCCP) [57,58] of the macrocyclic allylic sulfone with acrylates or acrylamides (Figure 1C).…”
Section: Introductionmentioning
confidence: 99%
“…Although radical substitution of shelf‐stable bis(thioacyl) disulfides and was used to synthesize RAFT agent under thermal conditions in situ , [6] they were sometimes confronted with a low efficiency of initiation. Recently, instead of thermal initiators, benzophenone derived photoinitiator (4‐methoxyphenyl) (4‐(trifluoromethyl)phenyl) methanone was selected to generate radicals through a hydrogen abstraction process [7] . The trithiocarbonate generated in situ was implemented in the polymerization of methyl acrylate, and narrowly distributed polymers with targeted molecular weights were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, instead of thermal initiators, benzophenone derived photoinitiator (4-methoxyphenyl) (4-(trifluoromethyl)phenyl) methanone was selected to generate radicals through a hydrogen abstraction process. [7] The trithiocarbonate generated in situ was implemented in the polymerization of methyl acrylate, and narrowly distributed polymers with targeted molecular weights were obtained. However, it was worth noting that bis(thioacyl) disulfides were obtained by oxidation of the corresponding carbodithionate salts, and it is necessary to remove the residual of oxidants.…”
Section: Introductionmentioning
confidence: 99%